The association between the COL12A1 gene and anterior cruciate ligament ruptures. Issue 16 (13th May 2009) - Posthumus, Michael; September, Alison V; O'Cuinneagain, Dion; van der Merwe, Willem; Schwellnus, Martin P; Collins, Malcolm
Abstract : Background: Anterior cruciate ligament (ACL) ruptures are among the most severe musculoskeletal soft tissue injuries. However, the exact mechanisms which cause these acute injuries are unknown. Recently, sequence variants within two genes, namely COL1A1 and COL5A1, which code for the α1 chains of types I and V collagen respectively, were shown to be associated with ACL ruptures. Type XII collagen, similarly to types I and V collagen, is a structural component of the ligament fibril and is encoded by a single gene, COL12A1 . Objective: The aim of this study was to investigate whether sequence variants within COL12A1 are associated with ACL ruptures. Methods: One hundred and twenty-nine (38 female) participants with clinically and surgically diagnosed ACL ruptures, as well as 216 (83 female) physically active controls participants (CON) without any history of ACL injury were included in this case-control genetic association study. All participants were genotyped for the Alu I and Bsr I restriction fragment length polymorphisms (RFLPs) within COL12A1 . Results: The AA genotype of the COL12A1 Alu I RFLP was significantly over-represented in the female (OR=2.4, 95% CI 1.0 to 5.5, p=0.048), but not male (p=0.359) ACL participants. There were no genotype differences between the ACL and CON group for the Bsr I RFLP. Conclusion: The COL12A1 Alu I RFLP is associated with ACL ruptures among female participants in this study. The results suggest that females with an AA genotype are at increased risk of ACL ruptures. These initial genetic association studies should be explored further and, if repeated, incorporated into multifactorial models developed to identify predisposed individuals.